Helicobacter pylori and Risk of Nonalcoholic Fatty Liver Disease - Karn Wijarnpreecha (2018)
© Copyright 2016 Wolters Kluwer Health, Inc. All rights reserved. Background/Objectives: Helicobacter pylori (H. pylori) is the most common chronic bacterial infection. Patients with H. pylori infection may be at an increased risk of nonalcoholic fatty liver disease (NAFLD) because of chronic inflammation and insulin resistance. Several epidemiologic studies attempting to determine this risk have yielded inconsistent results. This meta-analysis was conducted with the aims to summarize all available evidence and estimate the risk of NAFLD in patients with H. pylori infection. Methods: A literature search was performed using MEDLINE and EMBASE database from inception to June 2016. Studies that reported relative risks, odd ratios, or hazard ratios comparing the risk of NAFLD among patients with H. pylori infection versus without H. pylori infection were included. Pooled odds ratios and 95% confidence intervals were calculated using a random-effect, generic inverse variance method. Results: Six studies met our eligibility criteria and were included in this analysis. We found a statistically significant increased risk of NAFLD among patients with H. pylori infection with the pooled odds ratios of 1.21 (95% confidence interval, 1.07-1.37). The statistical heterogeneity was low with an I 2 of 49%. Conclusions: A significantly increased risk of NAFLD among patients with H. pylori infection was demonstrated in this meta-analysis. Further studies are required to clarify how this risk should be addressed in clinical practice.